1986
DOI: 10.1007/bf00379509
|View full text |Cite
|
Sign up to set email alerts
|

Water stress and light intensity effects on growth and nocturnal acid accumulation in a terrestrial CAM bromeliad (Bromelia humilis Jacq.) under natural conditions

Abstract: Seasonal variations in CAM performance of sunexposed and partially shaded populations of Bromelia humilis were measured under natural conditions in a semi-arid region in northern Venezuela. The sun population consisted of smaller plants, with lower chlorophyll and total nitrogen contents per unit leaf area compared with plants from the partial-shade population. During the dry season CAM activity, assessed as nocturnal acid accumulation, was higher in the partial-shade population. Acid accumulation was stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0
4

Year Published

1989
1989
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 6 publications
7
32
0
4
Order By: Relevance
“…This fact agrees with the findings of Medina et al (1986) and Medina (1987) who demonstrated that some epiphytic orchids native to tropical and subtropical forests incorporate atmospheric CO 2 at night, and show During the period of observation, both groups of plants developed new leaves (figure 3). Plants maintained under 90% of PAR started to develop a new leaf (LF 5) after 80 days ( figure 3A), whereas under 22.5% of PAR the appearance of LF 5 occurred only after 103 days from the start of the experiment ( figure 3B).…”
Section: Resultssupporting
confidence: 92%
“…This fact agrees with the findings of Medina et al (1986) and Medina (1987) who demonstrated that some epiphytic orchids native to tropical and subtropical forests incorporate atmospheric CO 2 at night, and show During the period of observation, both groups of plants developed new leaves (figure 3). Plants maintained under 90% of PAR started to develop a new leaf (LF 5) after 80 days ( figure 3A), whereas under 22.5% of PAR the appearance of LF 5 occurred only after 103 days from the start of the experiment ( figure 3B).…”
Section: Resultssupporting
confidence: 92%
“…com os alcalóides de Catharanthus roseus 100 . O efeito da seca na concentração de metabólitos é, às vezes, dependente do grau de estresse e do período em que ocorre, sendo que efeitos a curto prazo parecem levar a uma produção aumentada, enquanto a longo prazo é observado um efeito oposto 6,95,98,101,102 . Outro fator é que a chuva contínua pode resultar na perda de substâncias hidrossolúveis das folhas e raízes por lixiviação; sabe-se que isto se aplica a algumas plantas produtoras de alcalóides, glicosídeos e até mesmo óleos voláteis 47,101 .…”
Section: Disponibilidade Hídricaunclassified
“…In contrast, other studies indicate that the indirect positive effect can be outweighed by the direct negative effect (Pagès et al, 2003 andPagès andMichalet, 2003), thus precluding the occurrence of indirect facilitation (Levin, 1999;Brooker et al, 2008). In my study, CAM plants are thought to be shade tolerant because of their photosynthetic plasticity and acclimation to shade, as confirmed by experimental evidence (Medina et al, 1986;Fetene et al, 1990;Ceusters et al, 2011).…”
Section: Parameterization Of the Modelsupporting
confidence: 57%
“…In contrast, the photosynthetic plasticity of CAM plants and their acclimation to shade allows them to be shade tolerant (Medina et al, 1986;Fetene et al, 1990;Ceusters et al, 2011). Grasses and CAM plants are typically shallow rooted (Ogburn and Edwards, 2010; and thus they compete for soil water resources.…”
Section: Introductionmentioning
confidence: 99%